2016
DOI: 10.7575/aiac.alls.v.7n.3p.21
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian EFL Students’ Perspective on Writing Process: A Pilot Study

Abstract: The study was aimed at understanding the EFL Indonesian students' perspective on the writing process. The pilot study involved two male Indonesian postgraduate students in Universiti Utara Malaysia. The Indonesian students were selected based on the following criteria: (1) had enough knowledge in English writing, indicated by the completion of Academic Writing and Research Methodology courses taken in UUM; (2) had written an unpublished thesis during their undergraduate studies in Indonesia and they are writin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(12 reference statements)
1
5
1
Order By: Relevance
“…This finding is somewhat different from previous studies (e.g. Abas & Aziz, 2016;Ceylan, 2019), in which one of the writing problems is students have low interest in writing activities. This may due to the other factors that made the students interest in Essay Writing Course.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding is somewhat different from previous studies (e.g. Abas & Aziz, 2016;Ceylan, 2019), in which one of the writing problems is students have low interest in writing activities. This may due to the other factors that made the students interest in Essay Writing Course.…”
Section: Discussioncontrasting
confidence: 99%
“…Furher discussion, some of the interviewees also postulated that they did not always do the writing task according to the process of writing, because of the complicated ways in writing. Supporting to the results, Sadik in Abas & Aziz (2016) and Ceylan (2019) echoed the same statement that students experienced difficulty with the writing process in general, and skip the process in particular.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The condition as found by Abas and Aziz (2016) that Indonesian students faced difficulty in writing during the undergraduate study suggested the students to have a certain course that might help them to produce academic writing papers. Preparing the students for writing the final paper or Skripsi, Bina Nusantara (BINUS) University set a course that might help the students to write an academic research paper -English for Academic Writing course.…”
Section: Introductionmentioning
confidence: 99%
“…In many classes, writing comes in the form of copying and answering teacher"s instruction. In some cases of Universities in Indonesia, writing at times appears in mono mode system where students transform ideas based on certain topic given by teachers and it is emphasized more in the arrangement of vocabulary and structure hence they find writing in English to be difficult because they have to use the correct English grammar and vocabulary, apply the writing skills they have learnt, and incorporate these knowledge with their previous experience on the topic given when writing (Abas & Aziz, 2016). Yet, writing has "shifted from a relatively static and rigid approach to the teaching of writing (as a single lesson exercise) to consider writing as "a process" with a widening focus on the stages of writing" (Groves, 2010) that it is must not always be presented in the form of single mode as it can be in the form of multi modal by using images along with words (Bezemer & Kress, 2010;Lemke, 1998;Saidy, 2018).…”
Section: Introductionmentioning
confidence: 99%